Understanding the impact of urban form attributes on household vehicle ownership and choice in Metro Manila: Modeling, simulation, and application - Rith, Monorom (Animo Repository, 2019)
Projected economic growth is expected to further increase vehicle ownership among households in Metropolitan Manila. This increase is likely to translate to higher energy requirements, elevated greenhouse gas emissions and air pollution, as well as a worsening of traffic congestion. A multinomial logit-based household vehicle ownership model was developed taking into account household characteristics and urban form peculiarities that are hypothesized to affect the level of vehicle ownership among households. The model utilized data gathered from a survey of 2,300 households from various areas of Metropolitan Manila. Results indicated that flooding susceptibility of communities does not affect vehicle ownership and type among its residents. Higher public transport density and closer proximity to essential facilities and services were found to be strong determinants that discourage vehicle ownership. Higher population density, contrary to findings in most studies, tends to reinforce vehicle ownership due to the inadequacy of public transport service, especially in crowded areas. The model was used to simulate “what if” shares of levels of vehicle ownership and apply the model under scenarios of 1) access to essential facilities, 2) improved road public transport line density, and 3) their combination. The results indicated that these interventions, relative to the baseline scenario, could respectively reduce vehicles owned by 26.63%, 35.02%, and 59.61% among the households surveyed and CO2 emission by 1.33 million tonnes, 1.63 million tonnes, and 2.69 million tonnes. © 2019, Paulus Editora. All rights reserved.